Equine exploitation at Pompeii (AD 79). (April 2023) - Corbino, Chiara A.; Comegna, Chiara; Amoretti, Valeria; Modi, Alessandra; Cannariato, Costanza; Lari, Martina; Caramelli, David; Osanna, Massimo
Highlights: This paper investigates human-equid interactions at Pompeii in AD 79. Samples from urban and rural contexts have been included in this study. The multidisciplinary approach is based on zooarchaeology, archaeobotany and genetics. This paper offers an innovative and holistic approach of the human-equid relationship. The achieved results enrich our knowledge of everyday life in Roman towns. Abstract: Equids were an important component of Roman everyday life. Horses, donkeys and their hybrids (mule and hinny) have been used as pack animals for moving people and goods through time. The most prestigious horse breeds were often associated with the social status of the owner as some equestrian statues and written sources seem to suggest. However, management and exploitation of this taxon at that time is still largely unknown. This paper aims to investigate the human-equid relationship at Pompeii and to link the results to everyday life in a Roman town in the 1st century CE. Equid remains from several stables associated with urban houses and shops, as well as a rural villa have been subject to morphological, biometric, and ancient DNA (aDNA) analysis in order to enable their identification. The pathological evidence on the bones combined with ageing data has provided indications about the nature of the exploitation of these animals. Data on the fodder likely consumed by them were also obtained using previous studies to provide further hints about their management. The results indicate that equid individuals ranging from 4 to 8 years old were preferred at Pompeii. Horses were largely employed in a number of activities inside the town as well as in the countryside. This study, focused on the analysis of equids collected from the Pompeii stables, provides important information about the exploitation and management of this taxon in the Roman Imperial period.